The Correlation Between the Use of “Die with a Smile” Song by Bruno Mars and the Improvement of Pronunciation Ability at First Semester Student in English Education Department - Yusrotul Hasanah; Dinar Vincy Yunitaka Bahrudin; Linta Wafdan Hidayah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to explore the relationship between the use of the song ‘”Die with a Smile” by Bruno Mars and the improvement of pronunciation skills of first semester students in the English Education Department Universitas Islam Madura. The two variables in this research are the use of the song “Die with a Smile” as the independent variable (X) and the improvement of pronunciation skills as the dependent variable (Y). Using quantitative methods and Pearson correlation analysis, this research involved twenty-five students as samples, with data collected through tests and questionnaires. The results of the analysis showed that the correlation value was 0.588, which indicated a positive relationship with a moderate level correlation between the use of songs and students pronunciation ability. In addition, the significance value (Sig. 2-tailed) of 0.002 (p<0.05), which is smaller than 0.05, proves that the relationship is statistically significant indicating that the alternative hypothesis (Ha) accepted and the null hypothesis (H0) was rejected. Thus, the more often students use songs as a learning media, the better their pronunciation ability. However, because the correlation found was not entirely strong, this research recommends that the song learning method be combined with other approaches, such as direct phonetic exercises or the use of learning technology.